Efficacy of high-intensity interval-training compared to moderate-intensity continuous aerobic training on maximal aerobic potency in dogs: Randomized controlled clinical trial simple-blinded (2022)
ABSTRACT: Objective: To assess the efficacy of high-intensity interval-training (HIIT) compared to moderateintensity continuous training (MICT) on maximal aerobic potency in dogs. Methods: Randomized, simple-blinded controlled clinical trial, with three parallel groups for the purpose of demonstrating superiority of HIIT compared to MICT and control groups based on the primary outcome of maximal aerobic potency. Dogs, before initiating and after finalizing the training performed an incremental exercise test (IET) on a treadmill to obtain the maximal velocity reached (Vmax) and velocity at lactate threshold (VLT). Also resting parameters of heart and respiratory rate, left ventricular (LV) chambers (measurements and indexes) and systolic function were also measured. Dogs assigned to each intervention endured a 42-minute session of HIIT (n=11) or MICT (n=9) for 12-weeks. HIIT comprised four intervals of four minutes each at a load of 85% of VLT, alternating with a 4-minute resting period. MICT group had a continuous load of 60% of VLT. The control group (C) (n=10) remained in a cage. After the 12-week training program a confirmed trained state was determined by a ≥15% reduction in heart rate at rest (HRR)(1,2). Results: Among the 30 dogs included in the study, the mean age was 30.5±17.7 months and an initial weight of 17.6±10.3 kg, females were 46.7%, and the mean compliance was 94.5±14.3%. A statistically significant difference was observed between the medians of the maximum velocity (Vmax) at the end of the intervention of the HIIT group (14.4 km/h) compared to the MICT (12.8 km/h) (p=0.038) with a medium effect size (Rosenthal correlation of r = .46). Both medians of HIIT (12.8 km/h) (p<0.0001) and MICT (12.8 km/h) (p=0.010) compared to the control group (9.6 km/h) had a significant statistical difference 13 in VLT, with a very large effect size for the HIIT group (Rosenthal correlation of r = .86) and with a large effect size for the MICT group (Rosenthal correlation of r = .62). When comparing the medians of the before and after the intervention, both types of training had a significant statistical difference decrease on the respiratory rate at rest (RRR) with a very large effect size (Rosenthal correlation of r = .80). Among the dogs of the HIIT group, comparing before and after the intervention, a significant statistical increase was determined on VLT, left ventricular mass (LVM), left ventricular mass index (LVMI) and relative wall thickness (RWT), all with a large effect size (Rosenthal correlation of r = .67; .6; .67 and .72 respectively). Conclusions: HIIT was superior compared to MICT in increasing the maximal aerobic potency. Both aerobic trainings reduced the respiratory rate at rest at the end of the intervention.